2021
DOI: 10.3389/fonc.2021.641044
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Therapy in First-Line Gastric and Gastroesophageal Junction Adenocarcinoma: A Retrospective Analysis

Abstract: BackgroundFluoropyrimidine with platinum-based chemotherapy has become the standard of care for advanced gastric and gastroesophageal (GEJ) cancer. Trials in colon cancer show that induction chemotherapy followed by maintenance chemotherapy is an efficacious strategy to maximize clinical response while minimizing toxicity. The current retrospective study aims to evaluate the efficacy and tolerability of maintenance versus continuous treatment in advanced GEJ malignancy.MethodsA retrospective analysis of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Fluoropyrimidine and platinum-containing treatment is standard-of-care first - line chemotherapy for advanced gastric, gastroesophageal junction (GEJ) and colon cancer. 8 – 10 Response to treatment usually leads to a reduction in the extension of the neoplasm also in the intestinal lumen and as a results to a reduction in the risk of bleeding either spontaneously or induced by any anticoagulant treatment. DOACs often meet both patient’s and physician’s preference when antithrombotic therapy is required because there is no need of daily subcutaneous injection.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoropyrimidine and platinum-containing treatment is standard-of-care first - line chemotherapy for advanced gastric, gastroesophageal junction (GEJ) and colon cancer. 8 – 10 Response to treatment usually leads to a reduction in the extension of the neoplasm also in the intestinal lumen and as a results to a reduction in the risk of bleeding either spontaneously or induced by any anticoagulant treatment. DOACs often meet both patient’s and physician’s preference when antithrombotic therapy is required because there is no need of daily subcutaneous injection.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the potentials of ferroptosis in cancer therapy is a fast-growing field of study, where several ferroptosis inducers have been found to be beneficial and promising in pre-clinical studies [ 19 ]. Currently, fluoropyrimidine with platinum-based chemotherapy serve as the standard regimen in advanced GC, in which drug resistance occurs frequently [ 20 ]. Cancer cells exhibit an increased iron demand compared with normal cells, and the iron dependency can make cancer cells more vulnerable to ferroptosis and creates the potential of ferroptosis to be a new promising way to kill therapy-resistant cancers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%